Yesus: Tawaran yang Menggugat - Samosir, Leonardus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2005)
The message about Jesus the Christ is always contextual in nature. The message serves as the answer to particular quest, including the quest for basic orientation of life. It should be noted, however, that contextualization is also fragmentation which presupposes certain kind of functionalism.